Relationship Between Pain Intensity and Workload with The Functional Degree of Low Back Pain in Warehouse Workers at The BULOG Rice Warehouse in Cirebon City - Moh. Irwan Dharmansyah; Maryano Maryano; Kati Sriwiyati (CV. Publikasi Indonesia, 2026)
Low Back Pain (LBP) is a leading cause of global disability and often occurs among informal sector workers who are exposed to high physical loads, such as pelvic coolies. Pain intensity and workload are thought to play a role in the decline in functional capacity, but evidence concerning informal worker populations remains limited. This study aims to analyze the relationship between pain intensity and workload with the functional degree of LBP in pelvic coolies at the BULOG Rice Warehouse in Cirebon City. An analytical observational study with a cross-sectional design was conducted on 38 pelvic coolies who met the inclusion criteria. Pain intensity was measured using the Numeric Rating Scale (NRS), workload was categorized by force weight (<20 kg; 20–30 kg; >30 kg), and functional degree was measured using the Back Pain Functional Scale (BPFS). Bivariate analysis used the Spearman correlation test with a significance level of p<0.05. Most respondents experienced mild pain (52.63%) and a moderate workload (47.4%). The median functional degree of LBP was 55% ± 4.77%. There was a significant relationship between pain intensity and the functional degree of LBP (p=0.001; r=0.530) with moderate correlation strength and a positive direction. No association was found between workload and the functional degree of LBP (p=0.327; r=0.163). Pain intensity was significantly related to the functional degree of LBP in pelvic coolies, whereas workload did not show a meaningful relationship. The management of LBP in informal sector workers needs to focus on pain management and functional capacity improvement through rehabilitative approaches and work ergonomics.